INTERNALISASI NILAI KEDAMAIAN MELALUI PENDIDIKAN KEDAMAIAN SEBAGAI PENGUATAN PEMBANGUNAN KARAKTER PADA MASYARAKAT HETEROGEN - Mardan Umar (Waskita: Jurnal Pendidikan Nilai dan Pembangunan Karakter, 2017)
Indonesia has many diversities in many aspects. It is not only about hav- ing various ethnics but also many cultures, languages, as well as reli- gions. The diversity must be framed in the spirit of unity in diversities by internalizing the value ofpeace  as the embodiment of diversity. This review discusses the internalization ofpeace  values through peace educa- tion as a strengthening of character building in heterogeneous societies in Indonesia. This discussion covers the concept of values internalization, peace education, education policy, in heterogeneous societies and the ur- gency ofpeace  education recently. The main issues of this study are how to internalize the value ofpeace  education through peace education in educational institutions and the urgency ofpeace  education in hetero- geneous societies in Indonesia and how to strengthen nation character development through peace education in order to create a peaceful life in this country.The purpose of this study is to describe the internalization of the peace value through peace education of the urgency ofpeace  education in the context of heterogeneous communities in Indonesia and to describe the strengthening of character building through peace education in heteroge- neous societies in Indonesia to create a peaceful and safe life. The result of this study shows that the internalization ofpeace  values can be done by integrating the peace value through peace education, both using Religion, and Pancasila and Civil subject. The national education policy has also provided a space for heterogeneity of Indonesian society.However the policy has not explicitly put forward peace education as an effort to maintain the harmony of national diversity. Therefore the edu- cation ofpeace  should be put forward to strengthen the development of the heterogeneous ofI ndonesian character.